Piano: An instrument in contemporary times - Cárdenas Serván, Inmaculada (2021)
This research is divided in two parts, along with the conclusions, bibliography and discography. The first part is an approach of the environment and influences in the piano works done by the author between 2016 and 2020. These works, which will connect with sound design and biographical elements, based on her pedagogical theory. The second part focuses on the analysis of these piano works where Ensaio (2008) is included for piano, voice and live electronics as an antecedent.